1977
DOI: 10.1084/jem.146.5.1332
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cell immunoglobulin secretion. Arrest is accompanied by alterations the golgi complex

Abstract: Conditions influencing Ig secretion by plasma cells have been studied with suspensions of murine plasma cells and myeloma cells by determining the release of (3)H-Ig after a pulse of biosynthetic labeling with L- [4,5-(3)H]-leucine. Ig secretion is insensitive to a variety of hormones, mediators, cyclic nucleotide derivatives, extracellular calcium depletion, and agents acting on mierotubules or microfilaments; i.e., to a number of factors which are involved in the regulation of secretion by cells with a stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
167
2

Year Published

1980
1980
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(190 citation statements)
references
References 29 publications
21
167
2
Order By: Relevance
“…In principle, the accumulation of G protein in cytoplasmic vesicles may result from interiorization of surface molecules, or from impaired delivery to the cell surface of G molecules synthesized during the chloroquine treatment (45). These possibilities were examined in transfected cultures that re-ceived the protein synthesis inhibitor cycloheximide belbre (45 min) the addition of chloroquine, and were incubated for several hours in the presence of both drugs.…”
Section: Selective Endocytosis Of G Proteinmentioning
confidence: 99%
“…In principle, the accumulation of G protein in cytoplasmic vesicles may result from interiorization of surface molecules, or from impaired delivery to the cell surface of G molecules synthesized during the chloroquine treatment (45). These possibilities were examined in transfected cultures that re-ceived the protein synthesis inhibitor cycloheximide belbre (45 min) the addition of chloroquine, and were incubated for several hours in the presence of both drugs.…”
Section: Selective Endocytosis Of G Proteinmentioning
confidence: 99%
“…As a result of viral inhibition of host protein synthesis, only one or a few viral membrane glycoproteins are synthesized in infected cells. These viruses possess limited genetic capacity, and the glycosylation and transport of their membrane glycoproteins to the cell surface are probably carried out by the same systems used by the host cell for biogenesis of its own membrane glycoproteins.Monovalent ionophores such as monensin, which is reported to interfere with the translocation of secretory as well as most membrane glycoproteins, have been used to characterize the pathways of intracellular glycoprotein transport in eucaryotic cells (18,(37)(38)(39)(40)(41)43). In addition, the effects of monensin on IgM and H2 glycosylation in lymphoid cells and fibronectin glycosylation in cultured human fibroblasts, as well as its influence on oligosaccharide maturation of…”
mentioning
confidence: 99%
“…Monovalent ionophores such as monensin have served as useful probes for studying this process since they disrupt the intracellular flow without permanently damaging cells and they also have minimal effects upon energy production [ 13] and protein synthesis [4]. Monensin does cause substantial changes in cellular ultrastructure, affecting primarily mitochondrial and Golgi architecture [1,6]. Although fibroblasts are also affected in this way [6], we have found that, in the chondrocytes used here, both the Golgi elements and rough endoplasmic reticuhim are altered by the presence of monensin (unpublished).…”
Section: -mentioning
confidence: 99%